2018
DOI: 10.1002/cyto.b.21748
|View full text |Cite
|
Sign up to set email alerts
|

Novel DRAQ5™/SYTOX® Blue Based Flow Cytometric Strategy to Identify and Characterize Stem Cells in Human Breast Milk

Abstract: Background: Human breast milk could be an important stem cell source for the development of newborn and preterm infants, but quantitative data on the stem cell content in breast milk at various gestational stages are needed to determine the clinical value of breast milk as a source of stem cells. Breast milk also contains milk fat globules, lipid droplets of different sizes, debris and dead cells and these components hamper flow cytometry analysis of human breast milk samples.Methods: Here, we originally used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Whilst past publications may have considered all MESs in the pelleted fraction of milk as cells, our data corroborates recent findings suggesting that merely 9% of all pelleted MESs are HMCs [17]. Indeed, using both flow cytometry and fluorescence microscopy, we found that whilst a majority of MESs isolated from human milk absorb lipid stain Nile red, only a small subset are nucleated and incorporate DNA stains DRAQ5™ and/or Hoechst 33258 ( Fig.…”
Section: Immunofluorescence Microscopy Confirms Large Numbers Of Milksupporting
confidence: 91%
See 3 more Smart Citations
“…Whilst past publications may have considered all MESs in the pelleted fraction of milk as cells, our data corroborates recent findings suggesting that merely 9% of all pelleted MESs are HMCs [17]. Indeed, using both flow cytometry and fluorescence microscopy, we found that whilst a majority of MESs isolated from human milk absorb lipid stain Nile red, only a small subset are nucleated and incorporate DNA stains DRAQ5™ and/or Hoechst 33258 ( Fig.…”
Section: Immunofluorescence Microscopy Confirms Large Numbers Of Milksupporting
confidence: 91%
“…However, recovered live HMCs ranged from 5 to 27.6% of total expected HMCs, thereby lower than the previously reported number of live cells per sample (8 to 81% of HMCs) [17]. Further analysis should thereby assess whether any unaccounted live cells are retained inside of the column.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Keller et al have developed an improved protocol that use a recently developed staining agents DRAQ5™ far red and SYTOX ® blue for flow cytometry analysis of breast cells in human milk. This novel and reliable approach allowed to identify and quantify subpopulation of CD11b + monocytes as well as putative stem cells positive for cell surface markers TRA-1-81 and SSEA-4 [ 52 ]. Interestingly, for TRA-1-81 + putative stem cells the high variations were detected in samples without significant differences between the gestational age groups.…”
Section: Progenitor Cells Of Breast Milkmentioning
confidence: 99%